2019
DOI: 10.2134/jeq2019.01.0038
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Buildup Increases Carbon Dioxide Emissions from Redox‐Oscillating Upland Soils while Catalyzing Iron(III) Reduction and Phosphorus Desorption

Abstract: Humic substances comprise chemically and physically complex forms of organic C that are recognized to be involved in the catalytic cycling of electrons in diverse biogeochemical reactions. Recent investigations have indicated that humic substances existing in redox-dynamic terrestrial environments, such as intermittently wet soils, may be uniquely important for regulating greenhouse gas emissions. However, many relevant studies have relied on the use of commercially available humic substances and/or synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Certain anaerobic bacteria in anoxic sediments have been shown to couple the oxidation of CH 4 to the reduction of NO 2 − by uniquely producing their own O 2 from nitric oxide (NO), then using this O 2 to oxidize CH 4 to CO 2 under anaerobic/anoxic conditions [29]. Anaerobes can also use external or self-produced electron-shuttling compounds to catalyze extracellular reduction of terminal electron acceptors (e.g., Fe(III)) [2,30,31]. Further, anaerobic microbial biofilms can form on mineral surfaces, allowing for unique process such as nanowire and interspecies electron transfer [32][33][34] (Figure 1).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Certain anaerobic bacteria in anoxic sediments have been shown to couple the oxidation of CH 4 to the reduction of NO 2 − by uniquely producing their own O 2 from nitric oxide (NO), then using this O 2 to oxidize CH 4 to CO 2 under anaerobic/anoxic conditions [29]. Anaerobes can also use external or self-produced electron-shuttling compounds to catalyze extracellular reduction of terminal electron acceptors (e.g., Fe(III)) [2,30,31]. Further, anaerobic microbial biofilms can form on mineral surfaces, allowing for unique process such as nanowire and interspecies electron transfer [32][33][34] (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…Crystal order and reactivity of the Fe-(oxyhydr)oxides are significantly altered by soil redox oscillations, which further regulate C and nutrient cycling [16,28,[49][50][51]. For example, organic C forms co-precipitated complexes with Fe-(oxyhydr)oxides, where phosphorus (P) also strongly sorbs to Fe-(oxyhydr)oxides, and so Fe(III)-reducing bacteria can significantly impact the coupled C-Fe-P cycle during redox oscillations and dissimilatory Fe(III) reduction [30,41,52,53]. The microbiome of tropical soils has been shown to quickly respond to different redox-oscillating conditions and there are many biogeochemical pathways that may be hypothesized to shift due to climatedriven redox perturbations now and in the immediate future [16,38,46].…”
Section: Climate-driven Redox Perturbations In Soilmentioning
confidence: 99%
“…Because many relevant studies have relied on the use of commercially available humic substances and/or synthetic humic analogs, Wilmoth et al (2019) conducted an anoxic incubation study to investigate the regulatory and catalytic effects of increasing concentrations of site‐specific (i.e., native) humic acid in an Appalachian upland soil that experienced oscillating redox conditions. Extracted native humic acid was characterized using 13 C NMR, Fourier transform infrared spectroscopy, and total CHNS elemental analyses.…”
Section: Humic Substances In Environmental Processesmentioning
confidence: 99%
“…Results presented show that native humic acid was relatively enriched in aromatic and amino acid C. Increasing concentrations of native humic acid added at the start of soil incubations led to higher rates of carbon dioxide (CO 2 ) emission and microbial iron(III) [Fe(III)] reduction. In addition, Wilmoth et al (2019) conducted experiments with a synthetic humic acid‐analog containing 0.2 g anthraquinone‐2,6‐disulfonic acid (AQDS) kg −1 dry soil to investigate catalytic electron cycling by native humic acid and AQDS. Results suggested that the buildup of native humic substances, which are relatively rich in aromatic and amino acid C, led to globally relevant increases in CO 2 emissions, the redox cycling of Fe, and increased the availability of organic phosphorus (P) after transition to anaerobic conditions.…”
Section: Humic Substances In Environmental Processesmentioning
confidence: 99%